Assessment of the quality of abrasion-resistant plates welded joint - Górka J. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The article presents the analysis of the structure and properties of joints made of abrasion-resistant plates having the structure of chromium cast iron and welded with filler metals, the use of which aimed to provide the high abrasion resistance of the surface layer and good mechanical properties of the base material. The face layer of the joint was made using the MMA (Manual Metal Arc) welding method and the Fe-Cr-Nb-B type nanocrystalline filler metal. The root weld was welded using an austenitic filler metal, whereas the filling layer was welded using the MAG method with a low-alloy filler metal. The joints were subjected to non-destructive tests (visual tests and penetrant tests) as well as to mechanical properties tests. The research involved macro and microscopic metallographic tests, the determination of the grain size using an Xpert PRO X-ray diffractometer, and the EDS analysis of the chemical composition of the precipitates. The assessment of the operational properties of the joints based on hardness measurements, static tensile tests, bend tests as well as identifying the metal-mineral abrasive wear resistance were performed in accordance with ASTM G65 – 04 standards. The results of the abrasion resistance tests were referred to the HARDOX 400 steel reference specimen. Considering the tests results it was concluded that the used filler materials can assure the appropriate operational properties of welded abrasion-resistant plates.